Akurasi Pemetaan Kelompok Belajar Siswa Menuju Prestasi Menggunakan Metode K-Means (Studi Kasus SMP Pembangunan Laboratorium UNP) - Dewi, Sri; Defit, Sarjon; Yunus, Yuhandri (Rektorat Universitas Putra Indonesia YPTK Padang, 2021)
The quality of students in school has a lot of diversity, this makes students have different levels of understanding. This can be seen from the variety of student scores obtained on report card scores, this needs to be a concern for the school, especially teachers. One of them is by forming effective study groups so that every student has the opportunity to excel. So this research was carried out with the aim of helping schools, especially teachers, to map student study groups evenly based on student report cards obtained in Semester I to Semester IV. The method used was clustering with the K-Means algorithm on the report card scores of Class IX.C students at SMP Pembangunan Laboratorium UNP. The results in this study obtained 3 clusters of students, namely students with High Achievement, Achievement and Less Achievement. This research can be used as a guide for teaching teachers in making decisions about the formation of student study groups in Class IX.C.